2019
DOI: 10.1002/art.40800
|View full text |Cite
|
Sign up to set email alerts
|

Muscle Expression of Type I and Type II Interferons Is Increased in Juvenile Dermatomyositis and Related to Clinical and Histologic Features

Abstract: Objective. To evaluate the expression of type I interferon (IFNα/β)-and type II IFN (IFNγ)-inducible genes in muscle biopsy specimens from patients with juvenile dermatomyositis (DM) and to correlate their expression levels with histologic and clinical features.Methods. Expression levels of IFN-inducible genes and proinflammatory cytokines were assessed by quantitative polymerase chain reaction in muscle biopsy specimens from patients with juvenile DM (n = 39), patients with Duchenne's muscular dystrophy (DMD)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
40
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(46 citation statements)
references
References 35 publications
5
40
0
1
Order By: Relevance
“…However, few of them were identified as biomarkers or crucial genes in JDM yet. Functional enrichment analysis indicated that type I interferon signaling and various virus infection pathways were strengthened in JDM compared to HC, which is consistent with findings of previous studies (Moneta, Marafon & Marasco, 2019;Piper et al, 2018). IFIT5, IFI16 and MX2, interferon-stimulated genes, both nuclear transcriptional factors, were found to be upregulated in other autoimmune diseases but not in JDM (Wang et , 2019b;Zhang & Xu, 2019).…”
Section: Discussionsupporting
confidence: 87%
“…However, few of them were identified as biomarkers or crucial genes in JDM yet. Functional enrichment analysis indicated that type I interferon signaling and various virus infection pathways were strengthened in JDM compared to HC, which is consistent with findings of previous studies (Moneta, Marafon & Marasco, 2019;Piper et al, 2018). IFIT5, IFI16 and MX2, interferon-stimulated genes, both nuclear transcriptional factors, were found to be upregulated in other autoimmune diseases but not in JDM (Wang et , 2019b;Zhang & Xu, 2019).…”
Section: Discussionsupporting
confidence: 87%
“…The first IFN module was stable over the disease course and consisted of genes induced primarily by type I IFN, whereas the second and third IFN modules correlated with skin and renal disease activity, and the genes in these modules were equally induced by both types I and II IFN, suggesting a role for type II IFN in SLE. In juvenile DM, IFN‐γ transcripts have been identified in the muscle tissue of 11 untreated patients and co‐localized with inflammatory infiltrates and T cells . However, the role of type II IFN in DM has not been thoroughly explored using unbiased, data‐driven methods.…”
Section: Introductionmentioning
confidence: 99%
“…As we know, an IFN signature has previously been described to be elevated in dermatomyositis [42,43]. Because neopterin is produced in response to IFN-γ, the high level of neopterin in DM patients may represent an IFN response.…”
Section: Discussionmentioning
confidence: 99%